Using consultants to improve teaching - Knapper, Christopher; Piccinin, Sergio (San Francisco: Jossey-bass publishers, 1999)
Consultation to improve teaching is a common activity for faculty development center. In addition many faculty act as advisers to their coleagues through peer consultation. this volume examines the process of consultation from a number of perspectives, describe appropiate resources in the field, and provide practical advice on how to get the most out of the consultation process, wheter you are seeking or offering advice
Incluye index p.105-111
Keywords: Aprendizaje; Educación Superior